ARE DIRECTIVES DIRECTLY APPLICABLE? - (:unkn) unknown (ANKARA UNIV EUROPEAN UNION RESEARCH CENTRE, 2016)
The article seeks the answer to the question of whether directives are directly applicable. It argues that on which legal basis the justification of direct effect of directives is provided - either on the doctrine of estoppel or the principle of effet utile (effectiveness) - is principally important in order to resolve the issue of drawing the limits of direct effect of directives, in particular resolution of the issue of recognition of horizontal direct effect of directives. In that regard, the nature of directives as legal instruments, similarities and differences between directives and regulations, the distinct concepts of direct applicability and direct effect and their relationship are analysed to diminish the obscurity in the legal literature.
Keywords: Direct applicability; Direct effect; Effet utile